Animals in the Restoration Process: Progressing the Trends - Majer, Jonathan (Blackwell Science Inc., 2009)
A survey of fauna-focused papers in Restoration Ecology indicates that increased attention is being paid to this component of the biota. Although much of this work is for monitoring, a growing number of studies relate to the economic or ecological value of animals in restored land. There is still a bias toward vertebrates over invertebrates, although the proportion of invertebrate-focused papers is steadily increasing. Analysis of these papers suggests that greater synergy would have been obtained if standardized protocols had been used and, in the case of invertebrates, studies would have been more informative if species-level identifications had been obtained. Partnerships with industry should allow long-term studies to be performed, which would provide more reliable information than that yielded from chronosequence-type investigations.